Evaluasi Kinerja Tata Kelola Sampah Rumah Tangga: Studi Kasus Dinas Lingkungan Hidup Kabupaten Ogan Komering Ulu Timur Sumatera Selatan - muhammad dimas marsepta; Dodi Faedlulloh; Dewie Brima Atika (Administrativa : Jurnal Birokrasi, Kebijakan dan Pelayanan Publik, 2026)
Household waste management has become an increasingly complex environmental issue due to population growth, urbanization, and changes in community consumption patterns. In East Ogan Komering Ulu Regency, the increasing volume of household waste has not been balanced by adequate management capacity, resulting in suboptimal waste services. This study aims to evaluate the performance of household waste management governance implemented by the Environmental Agency of East Ogan Komering Ulu Regency and to identify the supporting and inhibiting factors affecting its implementation. This research employed a qualitative approach with a descriptive-evaluative design. Data were collected through interviews, observations, and documentation, and analyzed using Mahmudi’s performance evaluation model, which consists of input, process, output, and outcome dimensions. The findings indicate that the performance of household waste management governance remains suboptimal. Limitations in infrastructure, transportation fleets, and human resources were identified as major constraints. Waste management processes have not been carried out effectively or evenly, as reflected in the low level of waste sorting and community participation. Although the amount of collected waste has increased, it has not been sufficient to keep pace with the growth of waste generation. In addition, public awareness and satisfaction with waste management services remain relatively low. The study concludes that waste management performance is influenced by both technical and social factors; therefore, integrated improvements in infrastructure, institutional capacity, and community participation are necessary to achieve sustainable waste management.